SAT0098 Risk of Hospitalization for Serious Bacterial Infections in Patients with Rheumatoid Arthritis Treated with Biologics. Analysis from The Record Study of The Italian Society for Rheumatology. (15th July 2016) - Bortoluzzi, A.; Sakellariou, G.; Carrara, G.; Govoni, M.; Scirè, C.A.
Abstract : Background: Biological disease modifying antirheumatic drugs (bDMARDs) are widely used in treating rheumatoid arthritis (RA). There are concerns regarding the risk of serious infections related to these treatments, and scarce information on the impact of co-treatments. Objectives: To define the risk of serious infections in patients receiving bDMARDs, evaluating the effect of specific biologic agents and co-treatments in a large population-based sample of RA deriving from the administrative health database of the Lombardy region in Italy. Methods: Data were extracted from health databases of the Lombardy Region in the period between 1/1/2004 and 31/12/2013. Patients with RA, identified through a rheumatologist certified diagnosis (exemption code 006.714.0) and treated with bDMARDs (abatacept, adalimumab, certolizumab, etanercept, golimumab, infliximab, rituximab and tocilizumab) were included. Hospitalizations for bacterial infections were evaluated by the hospital discharge forms in the period of exposure to each biologic drug with the following diagnosis ICD9CM: 049.* or 320.*, 054.3 or 323.*, 681.*682.*, 421.*, 481.*482.*, 590.*, 711.*, 730.0*730.2*, 038.* or 790.7. The association between biologic drugs exposure and hospitalization for bacterial infections was assessed by survival models for competing risks, with time-dependent covariates. Results were presented as hazard ratios (HR) and 95% confidence intervals (CI), crude and adjusted for pre-specified confounders (sex, age, disease duration, Charlson comorbidity index, concomitant use of methotrexate, leflunomide, corticosteroids, NSAIDs, number of previous biologics and previous infections). Results: 4656 RA patients who had at least one bDMARD prescription for a total of 7601 exposures were included. 3603 were women (77.4%) with a mean age at first bDMARD exposure of 55.7 years (12.7 ± SD) and with a modal disease duration over 5 years. The factors associated with hospitalization with a definite bacterial infection are shown in figure . Considering etanercept as reference, the adjusted HR for infection was equal to 0.29 (95% IC 0.10 - 0.82) for abatacept, while it was not significantly different compared to other bDMARDs. Conclusions: Treatment with bDMARDs was not associated with an increase in hospitalized infection. The risk was lower with abatacept that confirmed to have a better safety profile. Disclosure of Interest: None declared